2021
DOI: 10.1101/2021.12.29.473693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape of human spinal cord cell type diversity at midgestation

Abstract: Understanding spinal cord generation and assembly is essential to elucidate how motor behavior is controlled and how disorders arise. The cellular landscape of the human spinal cord remains, however, insufficiently explored. Here, we profiled the midgestation human spinal cord with single cell-resolution and discovered, even at this fetal stage, remarkable heterogeneity across and within cell types. Glia displayed diversity related to positional identity along the dorso-ventral and rostro-caudal axes, while as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…An exciting future direction in the application of scRNAseq to developmental biology is in understanding differentiation of motor neurons during human development. While experiments involving nonhuman primates are costly, there is ample opportunity to perform descriptive postmortem single-cell transcriptomics and epigenomics during human development [92,93]. Using these techniques, we may garner key insights into the defining features that separate human motor neurons from those of other vertebrates.…”
Section: Developing An Integrated View Of Motor Neuron Differentiationmentioning
confidence: 99%
“…An exciting future direction in the application of scRNAseq to developmental biology is in understanding differentiation of motor neurons during human development. While experiments involving nonhuman primates are costly, there is ample opportunity to perform descriptive postmortem single-cell transcriptomics and epigenomics during human development [92,93]. Using these techniques, we may garner key insights into the defining features that separate human motor neurons from those of other vertebrates.…”
Section: Developing An Integrated View Of Motor Neuron Differentiationmentioning
confidence: 99%
“…Like neuronal subtype specification, astrocyte diversification is highly influenced by the transcriptional code patterning DV progenitors (Hochstim et al, 2008;Muroyama et al, 2005;Vue et al, 2014;Zhao et al, 2014). Interestingly, in line with descriptions in the mouse, a recent analysis of the midgestation human spinal cord have shown astrocytes with specialized DV transcriptional programs and gene expression signatures map also onto distinct anatomical domains (Andersen et al, 2021). In addition, studies in the Drosophila larval ventral nerve cord have shown that individual astrocytes are allocated to consistent positions with their arbors covering stereotyped territories of the neuropil (Peco et al, 2016).…”
Section: The Precise Allocation Of Va0 Cells and The Formation Of Ast...mentioning
confidence: 66%
“…Their study analyzed 17,354 nuclei from adult mouse lumbar spinal cord and founded seven major clusters. The fifth dataset was generated by Andersen et al (2021). Their study obtained transcriptomes of 112,554 cells and 34,884 nuclei from four samples of human spinal cord and indicated the cellular landscape of the human spinal cord, including α and γ MNs.…”
Section: Single-cell Transcriptome Datasetsmentioning
confidence: 99%